Sistematización, el teatro comunitario para la construcción de la obra Sueños en almíbar con el colectivo Usme Proyecto Teatral (2023)
This degree work seeks to support the process of an artistic-pedagogical experience that the master artist lived with the collective Usme Proyecto Teatral in the years 2021-2022. Sueños en almíbar is a play with emphasis on community theater, which addresses issues such as: the resistance of the peasant tradition against the unbridled expansion of the city in the countryside, the defense of water reserves and the archaeological find that is located in the El Carmen hacienda, located in the village of La Requilina in the town of Usme.